A key ABA biosynthetic gene OsNCED3 is a positive regulator in resistance to Nilaparvata lugens in Oryza sativa - Li, Jitong; Liu, Hao; Lv, Xinyi; Wang, Wenjuan; Liang, Xinyan; Chen, Lin; Wang, Yiping; Liu, Jinglan (Frontiers in Plant Science, 2024)
The gene encoding 9-cis-epoxycarotenoid dioxygenase 3 (NCED3) functions in abscisic acid (ABA) biosynthesis, plant growth and development, and tolerance to adverse temperatures, drought and saline conditions. In this study, three rice lines were used to explore the function of OsNCED3, these included an OsNCED3-overexpressing line (OsNCED3-OE), a knockdown line (osnced3-RNAi) and wild-type rice (WT). These rice lines were infested with the brown plant hopper (BPH; Nilaparvata lugens) and examined for physiological and biochemical changes, hormone content, and defense gene expression. The results showed that OsNCED3 activated rice defense mechanisms, which led to an increased defense enzyme activity of superoxide dismutase, peroxidase, and polyphenol oxidase. The overexpression of OsNCED3 decreased the number of planthoppers and reduced oviposition and BPH hatching rates. Furthermore, the overexpression of OsNCED3 increased the concentrations of jasmonic acid, jasmonyl-isoleucine and ABA relative to WT rice and the osnced3-RNAi line. These results indicate that OsNCED3 improved the stress tolerance in rice and support a role for both jasmonates and ABA as defense compounds in the rice-BPH interaction.